Successful clusters through successful communication: why clusters should be managed by Place Leaders - Ganske, Patricia; Carbon, Claus-Christian (Frontiers in Communication, 2023)
Communication is critical in a wide variety of fields. Successful intra-organizational communication plays a significant role in building trust by creating an environment that empowers leaders to lead effectively, motivates employees to work, and thus contributes to organizational performance. In the context of cluster management, communication within the cluster, especially between the cluster leadership and the often vast number of cluster members, plays a pivotal role in successful and effective cluster development. A cluster typically operates in a regional context characterized by multi-agent, multi-objective, multi-vision, and pluralistic processes, methods, competencies, expertise, and aims.Cluster leadership is usually associated with particular difficulties in addressing these challenges. The primary needs and demands to fulfill such a role are to bring together a large number of partly competing actors involved in a cluster, to build up a trustful and open network, to include different cultures, and to harmonize institutional agendas. The main aim is to develop and establish a common ground to communicate and coordinate joint work efforts, which can mutually benefit and create synergies. The present article conceptualizes Effective internal Cluster Communication and Place Leadership as determinants for successful cluster developments. Despite the multiplicity of actors and sometimes even competing interest groups, Effective Place Leader Cluster Communication (EPLCC) enables clusters to inspire common, cooperative, collaborative and synergetic ways of working together. This is key to cluster development, successful and goal-directed cluster operation, and a sustainable operation of the cluster.